The Influence of Free Shipping and Online Customer Reviews on the Shopee Platform on Purchasing Decisions of Students of the Faculty of Economics, Nias University - Reyan Janefata Zebua; Aferiaman Telaumbanua; Sophia Molinda Kakisina; Serniati Zebua (Economics and Business Journal (ECBIS), 2026)
This study investigates the role of acquisition premiums in mergers and acquisitions (M&A) and their impact on shareholder wealth, focusing on five major Indian deals in pharmaceuticals, retail, banking, steel, and renewable energy sectors. Potential synergies often justify acquisition premiums ranging from approximately 15% to 40% above target companies’ market values. However, market responses suggest that such premiums may not consistently result in value creation for acquiring firms' shareholders. Empirical findings reveal mixed outcomes: Sun Pharma’s acquisition of Ranbaxy led to a 9.8% share price increase within five days, while Tata Steel’s high-premium acquisition of Bhushan Steel saw only a 1.7% gain. In contrast, deals like Reliance–Future Retail and Tata Power–Welspun Power showed minimal or negative returns, despite sizable premiums. These patterns indicate that premium size alone is not a reliable predictor of post-deal shareholder wealth creation. The study concludes that M&A success depends more on strategic fit, market timing, and sectoral dynamics than on the premium offered. This analysis contributes to the broader M&A discourse by offering evidence-based insights into how premium valuations can either maximise or dilute shareholder value, aiding investors, corporate strategists, and policy analysts in deal assessment.